The “Instructional Design 101” Course: Development of a Commercial Online Course with Microlearning Approach - Shabrina, Masyitha Nur; Hardika, Hardika; Dio Lingga; Muttaqin, Nabil (LPPM Universitas Terbuka, 2024)
In light of the burgeoning advancement of digital technologies and the subsequent rise of online courses, this study seeks to explore the commercial potential of an online course titled